Soil carbon stocks in tropical pasture systems in Colombia’s Orinoquía region: supporting readiness for climate finance - Villegas, Daniel Mauricio; Bastidas, Mike; Matiz Rubio, Natalia; Ruden, Alejandro; Rao, Idupulapati M.; Hyman, Glenn G.; Arango, Jacobo; Baedeker, Tobias; Cando, Lee; Ramírez Diaz, Mariangela; Teillard, Felix; Costa, Ciniro (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Key messages: ■ Using field measurements, it was found that pastures in clay soils in the Orinoquía region can store as more than 200 tCha-1 (0-100 cm). Results are 40% higher than the IPCC default values (0-30cm). ■ Close to 30% of the total SOC stock were found in the top 0-20 cm soil layer, highlighting the importance of evaluating deeper soil layers in SOC assessments. ■ Improving pasture systems have the potential to accumulate SOC, especially in the topsoil layer. This may be a consequence of higher forage production in improved pastures and cattle waste depositions. ■ Clay soils in Orinoquía shows a large potential for SOC sequestration through pasture improvement (~2.0 tCha-1y-1; 0-20 cm). This rate should be reduced overtime once SOC stocks approach a new steady-state. Therefore, future monitoring is critical to validating findings and better understanding SOC changes in the region. ■ This info note reports high sequestration potential for grassland in Colombia's Orinoquía region, which can be attractive for climate finance. Information is also provided to improve SOC estimation and implement SOC monitoring systems.